2021
DOI: 10.1111/pai.13707
|View full text |Cite
|
Sign up to set email alerts
|

Increased food diversity in the first year of life is inversely associated with allergic outcomes in the second year

Abstract: Background The evidence on the relationship between diet diversity in early life and allergic outcomes was few and inconsistent. We sought to determine the association of food diversity in the first year of life with allergic outcomes in the second year. Methods Two thousand two hundred fifty‐one mother‐infant pairs from Tongji Maternal and Child Health Cohort (TMCHC) were involved in the study. Information on complementary foods introduction was obtained by telephone interview at 6‐ and 12‐month postpartum fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 23 publications
0
34
0
1
Order By: Relevance
“…For example, in Zhong, Stampfli, and other studies, almost all infants at 12 months of age were introduced to vegetables, fruits, and meat, but a small number of people ate only peanuts and other nuts. 13,14 Stampfli found that the group with a high food diversity consumed more dairy products, eggs, and other foods than the group with a low level of food diversity. After adjustment, it was found that eating dairy products may have a protective effect on allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in Zhong, Stampfli, and other studies, almost all infants at 12 months of age were introduced to vegetables, fruits, and meat, but a small number of people ate only peanuts and other nuts. 13,14 Stampfli found that the group with a high food diversity consumed more dairy products, eggs, and other foods than the group with a low level of food diversity. After adjustment, it was found that eating dairy products may have a protective effect on allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…12,26 Zhong et al found that food diversity at 6 months old had a preventive effect on skin-related atopic disease, while there was no protective effect on food allergy, but food diversity at 12 months old had a preventive effect on food allergy and atopic dermatitis. 14 Stampfli et al reported that even if food diversity is high in the first year of life, insufficient food diversity in the second year remains a risk factor for developing allergic disease later in life. 13 It can be seen that only a variety of foods in a specific period may have a protective effect on atopic diseases, and this protective effect may be time-sensitive and requires the continuous intake of diverse foods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…С другой стороны, слишком раннее введение прикорма (до 4-6 месяцев), наоборот, может стать предиктором развития аллергических реакций [14,15]. Упоминаемое выше разнообразие продуктов важно не только для формирования правильного пищевого поведения, но и для предупреждения развития аллергии [16], что подтверждается исследованиями, в которых однообразное питание приводило к большему риску аллергических реакций в возрасте 1-2 лет [17].…”
Section: B пищевое поведениеunclassified